Oracle big data handbook plan and implement an enterprise big data infrastructure - Plunkett, Tom 1967-; Macdonald, Brian; Nelson, Bruce; Sun, Helen; Hornick, Mark F.; Laker, Keith; Mohiuddin, Khader; Harding, Debra L.; Segleau, David; Mishra, Gokula; Stackowiak, Robert (McGraw-Hill Education, 2014)
"Cowritten by members of Oracle's big data team, [this book] provides complete coverage of Oracle's comprehensive, integrated set of products for acquiring, organizing, analyzing, and leveraging unstructured data. The book discusses the strategies and technologies essential for a successful big data implementation, including Apache Hadoop, Oracle Big Data Appliance, Oracle Big Data Connectors, Oracle NoSQL Database, Oracle Endeca, Oracle Advanced Analytics, and Oracle's open source R offerings"--Page 4 of cover.